HASIL AIR HUTAN JATI PADA DUA SUB DAERAH ALIRAN SUNGAI DENGAN LUAS BERBEDA (Water yield of Teak Forest at two different catchment sizes) - Tyas Mutiara Basuki; Rahardyan Nugroho Adi; Edi Sulasmiko (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2017)
Effects of catchment sizes on hydrological responses were still being debated. Therefore, a study on hydrological effects of different catchment sizes was conducted in teak catchments. The catchments were Cemoro and Modang with their sizes were 13.5 and 3.4 km2, respectively. Research sites were in Forest Management Sub Unit (BKPH) Pasar Sore, Forest Management Unit (KPH) Cepu, and administratively were located in Blora Regency. Physical conditions of these catchments were similar. Rainfall was measured everyday at 07.00 a.m. Stream Water Level (SWL) data were collected from tide gauge measurements which were constructed at the outlet of the catchments. Discharge data were obtained by convertion of the SWL into discharge based on regression equations between direct discharge measurements in the field and SWL. Data analysed from 2001 to 2015 showed that Cemoro catchment had higher annual runoff than Modang. Generally, monthly runoff from Cemoro catchment was higher than Modang catchment, only for several years the Modang catchment had higher monthly runoff than Cemoro catchment. Annual runoff coefficient of Cemoro catchment was always higher than Modang catchment during 2001 to 2015. The runoff coefficient ranged from 0.20 to 0.62 and from 0.06 to 0.38 for Cemoro and Modang catchments, respectively.